EAST MEDITERRANEAN GEOPOLITICAL ENERGY ELBOWING WITH AN AMERICAN, RUSSIAN, ISRAELI, TURKISH, AND IRANIAN PREFIX: THE ROLE OF INTERNATIONAL AND REGIONAL ACTORS - N. MARKETOS, Thrassy (CENTRAL ASIA AND THE CAUCASUS, 2013)
The Leviathan gas deposit discovered in the Eastern Mediterranean Israeli Exclusive Economic Zone (EEZ) in 2010 by the U.S. Noble Energy Company is, in fact, Syria’s stake in “democratization.” The drilling of natural gas has given birth to a new conflict in the region, with Israel, Syria, and the Gaza Strip all claiming drilling rights. Cyprus, an EU member country, has not given up either, nor has Lebanon, which asked the U.N. to recognize its right to drill in its territorial waters, with Hezbollah being the most vocal in this regard. Turkey presented Syrian President Bashar al-Assad with the project of a Qatar-Saudi Arabia-Iraq-Syria-Turkey gas pipeline, through which natural gas could have been exported to Europe, to the detriment of the Russian Federation; however, the Syrian President refused, opting for Iran’s natural gas pipeline project instead.